TAVI in nonagenarians, what do we know so far? - Pablo Díez-Villanueva; Fernando Rivero (REC: Interventional Cardiology (English Ed.), 2021)
Transcatheter aortic valve implantation (TAVI) has become a widely used therapeutic strategy to treat symptomatic severe aortic stenosis. Certain randomized clinical trials available have already described the prognostic benefit of this technique in elderly patients with high or very high surgical risk. Also, when implanted via transfemoral access, it has proven non-inferior or even superior compared to surgical aortic valve replacement in low- and intermediate-risk patients. Therefore, the current recommendations support its use in elderly patients with severe aortic stenosis regardless of their surgical risk.1 However, since it is an age-related heart valve disease without an effective medical therapy yet, the prevalence of severe aortic stenosis has been growing parallel to life expectancy. As a matter of fact, this disease has huge repercussions in the patients’ survival rate and quality of life.2 Consequently, nonagenarian patients with severe aortic stenosis are a group in continuous expansion, and, to this date, the best way to treat them is still under discussion. Since most of these patients have traditionally been misrepresented in the clinical trials and there are registries with good results but a possible selection bias, the decision to treat these patients with TAVI is still challenging and is made on an individual...